Jackson-Type Inequalities in the Space $S^p$ - Voitsekhivs'kyi, V. R. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
In the case of approximation of periodic functions in the space $S^p$, we determine the exact constants in Jackson-type inequalities for the Zygmund, Rogosinski, and de la Valleé Poussin linear summation methods.